DAMPAK TINGKAT KESEHATAN BANK TERHADAP PERUBAHAN HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG GO PUBLIC DI BURSA EFEK INDONESIA (BEI) - Takarini, Nurjanti; Hayudanto Putra, Ukki (Jurnal Riset Ekonomi dan Bisnis, 2010)
Banking firm is one of the industries participating in the capital markets. This analysis is to determine the company's financial performance by using ratios. To assess the soundness of banking used CAMELS method of Bank Indonesia, which is standard in assessing bank soundness. On the basis of this conceptual study aims to determine the impact of CAR, RORA, NPM, ROA and LDR to changes in stock prices at the banking company that went public on the Indonesia Stock Exchange (IDX).The sample was determined by purposive sampling technique in order to obtain samples representative accordance with the specified criteria. The sample in this study there were 17 banking companies. This study uses secondary data in the form of financial statements of the period 2007-2009 which was published in print Indonesia (Info Bank), the Indonesian Capital Market Directory (ICMD) and the Indonesian stock exchange (IDX). To meet the research objectives, hypotheses were tested using multiple regression analysis.From the analysis it can be concluded that, CAR has an impact on stock price changes on the banking company that went public on the Indonesia Stock Exchange (IDX). As for the NPM, ROA and LDR have no impact on stock price changes on the banking company that went public on the Indonesia Stock Exchange (IDX).Keywords: bank soundness (CAMEL), stock price changes